Restoration of Trust in Toxic Relationships - Mary Philia Elisabeth; Evanda Danara Uthama (Budapest International Research and Critics University, 2022)
This study uses a qualitative method with a phenomenological paradigm that examines the recovery process of someone who has an infidelity in dating. A person's perspective and attitude towards a dating relationship will affect the quality of a courtship relationship. Toxic relationships or unhealthy romantic relationships can cause serious problems in relationships. Some of the negative impacts experienced by someone who was cheated on, one of which is a decreased sense of trust when going back to build a relationship with someone else and a sense of self-blame. It takes a long time to recover the emotions and trust that have been betrayed. The researcher tried to find out more deeply about the uniqueness of the recovery process of each participant and the trust that was formed in that process. This study was supported by two participants who underwent seven recovery processes according to Marshall (2016), although their different infidelity experiences made the process not sequential. The environmental assistance and the desire from oneself made the participants' trust in themselves increase, both in their relationships with other people and in their self-confidence.